2008
DOI: 10.1007/s11095-008-9553-z
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of NFκB and its Regulated Gene Products by Oral Administration of Green Tea Polyphenols in an Autochthonous Mouse Prostate Cancer Model

Abstract: Purpose-This study examines the role of cell survival/apoptosis related proteins involved in NFκB signaling pathways and its associated events in GTP-induced chemoprevention of prostate cancer in TRAMP mice.Methods-Mice were given 0.1% GTP as drinking fluid. Western blot and immunohistochemical analysis performed to examine NFκB and its regulated pathway in response to GTP.Results-Our data demonstrated increased expression of NFκB, IKKα, IKKβ, RANK, NIK and STAT-3 in dorso-lateral prostate of TRAMP mice as a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 30 publications
2
45
0
Order By: Relevance
“…The administration of green tea polyphenols caused a decrease in the levels of OPN in TRAMP mice [180]. This was attributed to reduce levels and activity of NF-B, a transcription factor that upregulates OPN expression [92].…”
Section: Therapeutic Targeting Of Opnmentioning
confidence: 99%
“…The administration of green tea polyphenols caused a decrease in the levels of OPN in TRAMP mice [180]. This was attributed to reduce levels and activity of NF-B, a transcription factor that upregulates OPN expression [92].…”
Section: Therapeutic Targeting Of Opnmentioning
confidence: 99%
“…In view of these reports, down-regulation of NF-κB by tea polyphenols might be correlated with induction of apoptosis and thus contributes to its anti-cancer effects in DEN-induced lung tumors. Inhibition of NF-κB by tea polyphenols has been reported in vitro and in vivo conditions [43][44][45]. Nam et al [46] reported that Epigallocatechin-3-gallate (EGCG) the major constituent of GTPs, inhibits proteasome function, a mechanism known to inhibit NF-κB activity, at concentrations of EGCG that are seen in the serum of green tea drinkers, suggesting its role in treatment also.…”
Section: Discussionmentioning
confidence: 99%
“…There was increased expression of NF-κB, IKKα, IKKβ, RANK, NIK and STAT-3 in dorsolateral prostate of TRAMP mice as a function of age and tumor growth and continuous GTP treatment caused significant decrease in the levels of these proteins. There was also a shift in the balance between Bax and Bcl2 proteins favoring apoptosis by GTP treatment via inhibition of NF-κB signaling [15]. Hsu et al, [16] have recently examined the effects of dietary soy and tea on NF-κB activation and inflammation in-vivo using male Noble rats implanted with estradiol and testosterone, which is a hormone-induced rat model for PCa.…”
Section: Effect Of Green Tea Polyphenols On Nuclear Factor (Nf)-κb Simentioning
confidence: 99%